KWS Pathfinder: Patient Triaging Web System At Klinik Warga SASMEC@IIUM - Edre, Mohammad Aidid; Saidin, Nur Amira; Mohd Nasaruddin, Nur Asifa (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: Klinik Warga SASMEC@IIUM (KWS) provides care for non-critical cases, but we faced issues with patients requiring urgent treatment at the Emergency and Trauma Department (ETD) coming to our clinic and vice versa which led to increasing the burden and waiting times at our clinic. To resolve this, we created KWS Pathfinder, a digital triaging tool to better direct patients to either KWS or ETD as needed. This research aimed to develop, validate, and assess the effectiveness of the KWS Pathfinder application in improving patient triage and management. Methods: This cross-sectional study analyzed 326 patient records from Klinik Warga SASMEC between October 2023 and August 2024, assessing variables such as symptoms, vital signs before the clinic visit, and clinical outcomes. The study utilized triaging criteria adopted from Emergency Medicine and Trauma Services Policy (EMTS) and a few other guidelines, incorporating these into an interactive web application developed using Python software by our Public Health Specialist. The questionnaires were validated by two Emergency Physicians and implemented by the clinic's healthcare providers. Data was analyzed using Microsoft Excel. Results: At Klinik Warga SASMEC, 68.8% of patients are staff members, while the remaining patients are their first-degree relatives. Among those who completed the questionnaire, 8.6% exhibited symptoms that required emergency treatment, and 88.7% of all respondents were accurately triaged. By utilising the KWS Pathfinder application, we observed that 6.7% of respondents were promptly directed to ETD and received the necessary treatment, which not only alleviated the workload and burden on KWS staff but also reduced patients waiting times. Conclusion: KWS Pathfinder is a user-friendly digital application designed to minimize the risk of incorrect triaging, thereby reducing patient waiting times, morbidity, and mortality. It also empowers both patients and staff, ensuring that individuals receive the appropriate treatment at the right facility. International Journal of Human and Health Sciences Supplementary Issue 02: 2024 Page: S20